2006
DOI: 10.1111/j.1740-0929.2006.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an environmental enrichment using a drum can on behavioral, physiological and productive characteristics in fattening beef cattle

Abstract: To evaluate the effects of environmental enrichment on behavioral, physiological and productive characteristics, 71 Japanese Black × Holstein steers (8 months of age; 299.5 ± 22.6 kg) were allocated to three pens in two repetitive experiments. Pen C (n = 11 and 12) consisted of a feeding alley for grain feed, a trough for dry hay, a water bowl and a resting space as a control pen. Pen D (n = 12 and 12) included a drum can (58 cm diameter ×90 cm height) containing hay. Pen GD (n = 12 and 12) included a drum can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
3
21
2
Order By: Relevance
“…Furthermore, a lack of relationship between feather CORT and the behaviors we measured suggests that relying solely upon behavioral measures of stress to assess captive animal well-being can be misleading, an assertion supported by other studies [19], [20], [39], [40], [43]. We are not suggesting that enrichment is harmful to captive animals.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, a lack of relationship between feather CORT and the behaviors we measured suggests that relying solely upon behavioral measures of stress to assess captive animal well-being can be misleading, an assertion supported by other studies [19], [20], [39], [40], [43]. We are not suggesting that enrichment is harmful to captive animals.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies provided in non-canine species found that after stress tests there is a change in both behavior and physiology [10], while other studies found changes only in physiology or only in behavior [11], [12]. This suggests that behaviour and stress physiology in some cases may operate independently of each other.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies investigate the psychological aspects of animals in terms of freedom to express normal behavior and freedom from fear and distress. Environmental enrichment as one of the methods for improv-ing animal welfare in intensive animal husbandry is known (Takeda 2007) and has been studied in cattle (Pelley et al 1995;Wilson et al 2002;Ishiwata et al 2006;Kohari et al 2007). However, there are few studies regarding environmental enrichment in terms of the five freedoms (Young 2003).…”
Section: Introductionmentioning
confidence: 99%